2014
DOI: 10.1186/2193-1801-3-78
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cervical muscle fatigue on the perception of the subjective vertical and horizontal

Abstract: IntroductionCervical functional capacity outcome measures that are simple and reliable are urgently needed in order permit accurate assessment/reassessment during treatments and rehabilitation. Induced neck muscle fatigue has been shown to alter functional capacities such as balance and kinaesthetic sense in the standing posture. The Rod and Frame Test has also shown promise as a method of assessing the effects of chronic neck pain and injury, but currently only in the sitting position. The objectives of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
3
1
1
Order By: Relevance
“…In our study, verticality measurements were performed in a sitting position. The RFT does not seem to be affected by the subject's position at the time of recording, but the verticality estimation error seems to increase with muscle fatigue in healthy subjects [52]. However, in our study with patients with FMS, we did not find a correlation between the severity of fatigue and MAE-RFT, although we did find a correlation with the MAE-SVV test.…”
Section: Discussioncontrasting
confidence: 82%
“…In our study, verticality measurements were performed in a sitting position. The RFT does not seem to be affected by the subject's position at the time of recording, but the verticality estimation error seems to increase with muscle fatigue in healthy subjects [52]. However, in our study with patients with FMS, we did not find a correlation between the severity of fatigue and MAE-RFT, although we did find a correlation with the MAE-SVV test.…”
Section: Discussioncontrasting
confidence: 82%
“…Well-differentiated non-invasive papillary tumors were predominately characterized by an increase in ST6GAL1 expression, while invasive tumors (pT2-4) displayed a significant decrease in ST6GAL1 expression. Such disparity is, however, hardly surprising as both tumor forms are characterized by a unique molecular profile, which extends to the epigenetic level [ 8 , 10 , 29 ]. In addition, Seales et al showed that expression of oncogenic RAS in HD3 colonocytes caused an increase in α-2,6-sialylation of β1-integrins by ST6GAL1, and the expression of dominant-negative RAS results in decreased sialylation [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of aberrant DNA methylation has rapidly garnered interest in cancer risk assessment, diagnosis, as well as prognosis and therapy monitoring [ 33 , 34 ]. The progressive increase in de novo methylation of CpG islands in urothelial carcinoma suggests that epigenetic gene silencing is involved in the development of UC [ 10 ]. Interestingly, Fleischer et al has previously shown that the ST6GAL1 promoter sequence contains distinct CpG islands whose DNA methylation caused loss of ST6GAL1 expression in breast cancer [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vielen Studien wird jedoch gezeigt, dass die HWS einen Einfluss auf die Okulomotorik 43 , 44 , 45 , 46 , 47 , 48 , auf das Gleichgewicht 35 , 49 , 50 , 51 , 52 , 53 , 54 , 55 und auf die Raumorientierung 48 , 56 , 57 , 58 , 59 hat. Ermüdbare oder ermüdete Nackenmuskeln können sowohl die Raumorientierung 60 als auch das Gleichgewicht 61 , 62 , 63 beeinflussen. Obwohl diese Zusammenhänge belegt sind, bleibt es schwierig, den zervikogenen Schwindel nachzuweisen, da es hierfür keinen eindeutigen Test gibt.…”
Section: Zervikogener Schwindelunclassified